Transitional care gaps and caregiver burden after ICU discharge: a cross-sectional study of patient–caregiver dyads - Hongfei Wang; Ning Luo; Yin Li (Frontiers in Public Health, 2026)
Background Survivors of critical illness experience post-intensive care syndrome (PICS), and family caregivers bear a parallel burden, PICS-family, while gaps in transitional-care services persist. We aimed to determine the prevalence of a high transitional-care gap after intensive care unit (ICU) discharge (primary outcome) and to assess whether it was associated with caregiving burden and psychological strain; a secondary aim was to assess residence-related access barriers. Methods A single-center cross-sectional study of patient–caregiver dyads at Tianjin First Central Hospital, China, from February 2022 to March 2026, using consecutive sampling (2,270 of 2,981 eligible dyads; 76.1%). Eligible dyads comprised a patient aged ≥18 years with an ICU stay ≥24 h who survived to hospital discharge and an unpaid primary family caregiver. Caregivers were assessed once, at a mean of 21.3 (SD 4.4) days after ICU discharge, using a researcher-developed eight-domain battery. The primary outcome was a high transitional-care gap (≥5 unmet services of 15). Rehospitalization or emergency department (ED) visit was defined as unplanned readmission or ED attendance between hospital discharge and assessment. Analyses were conducted in R version 4.3.2 using chi-square tests, Spearman correlation, and multivariable linear and logistic regression. Results All measures were completed by the family caregiver, reporting on both dyad members. Among 2,270 dyads (patient age 57.4 ± 14.4 years; 43.6% women; 65.3% mechanically ventilated), patient-level outcomes were rehospitalization/ED visit in 576 (25.4%) and mean vulnerability 28.5 ± 5.3; caregiver-level outcomes were a high transitional-care gap in 1,710 (75.3%; 95% CI 73.5–77.1), high burden in 761 (33.5%), and mean strain 27.5 ± 4.1. Unmet need was highest for psychological support of the caregiver (76.8%) and patient (74.2%). A high gap was not associated with greater burden: 22.1 ± 7.7 with a high gap versus 23.1 ± 7.8 without (SMD ≤ 0.14), and the unmet-need score did not predict burden after adjustment ( β = 0.00, 95% CI − 0.02 to 0.01, p = 0.69). Burden was predicted by caregiving hours/day ( β = 0.83, 95% CI 0.81–0.85, p < 0.001; adjusted R 2 = 0.876), and strain by burden ( β = 0.73) and patient vulnerability ( β = 0.25; both p < 0.001). Furthermore, rural caregivers reported more of the 13/14 access barriers (high barrier burden 52.5% vs. 26.9%; prevalence ratio 1.95, p < 0.001) without higher gaps, burden, or rehospitalization (all p > 0.19). Conclusion Three-quarters of dyads left the ICU with a high transitional-care gap, concentrated in psychological support. However, the gap was not associated with caregiver burden, which was measured by caregiving intensity and patient dependency. Service expansion and caregiver support are therefore distinct targets, and neither measure identifies the families needing the other.